Dampak Olahraga Kuratif Terhadap Kesehatan - Dianta Saragih; Dedek Sinaga; Dian Rizky; Ricky Sihite; Nimrot Manalu; Miftahul Ihsan; Andes Martua (CV. ITTC INDONESIA, 2025)
Curative exercise is a form of physical activity used as part of therapy to treat various health conditions. This study aims to analyze the effectiveness of curative exercise in improving the quality of life of patients with chronic diseases. The research method used is literature study and data analysis from various related journals. The results of the study indicate that curative exercise has a significant role in improving body function, reducing disease symptoms, and improving patient mental well-being.